2022
DOI: 10.1108/f-07-2021-0067
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of spatial configuration on visitors’ spatial cognition in health-care spaces: case studies in Gilan, Iran

Abstract: Purpose This study aims to explore the impact of spatial configuration on behavioral patterns of visitors in the ground floor of health-care spaces. Design/methodology/approach In this study, the Space Syntax analysis was used to combine visibility graph analysis and axial line analysis with empirical observation of visitors’ activities. Two types of observation methods on visitors were conducted to discover the behavioral patterns of individuals, respectively, named “gate counts” and “people following.” F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Liao et al [54] identified that the spatial pattern of historic Chinese towns and cities consists of axiality and concentric approaches which seems to have originated from traditional culture and ideologies. Further empirical studies declared that spatial arrangements have a significant influence on spatial cognition and the way that visitors perceive public spaces [55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liao et al [54] identified that the spatial pattern of historic Chinese towns and cities consists of axiality and concentric approaches which seems to have originated from traditional culture and ideologies. Further empirical studies declared that spatial arrangements have a significant influence on spatial cognition and the way that visitors perceive public spaces [55].…”
Section: Literature Reviewmentioning
confidence: 99%